What's inside a caterpillar cocoon? : and other questions about moths & butterflies - Ignotofsky, Rachel, 1989- (Crown Books for Young Readers, 2023)
"Have you ever wondered what happens inside a caterpillar cocoon? Or how moths and butterflies are related? Or what the difference is between a cocoon and a chrysalis? Wonder no more!"--